A Pragmatic Analysis of Speech Acts of Muhaimin Iskandar in the First Debate of the Vice-Presidential Candidates 2024 - Wibowo, Hanafi; Elda Anggraini, Cindi (Program Studi Magister Tadris Bahasa Inggris UIN Sultan Maulana Hasanuddin Banten, 2024)
The aim of this research is to analyze the locutionary and illocutionary acts carried out by Muhaimin Iskandar in the first debate for vice presidential candidates in the 2024 Indonesian presidential election. This research seeks to examine the specific linguistic and communicative strategies used by Muhaimin Iskandar, including his communication style, techniques persuasive, and rhetorical strategies used in debates. By interpreting the meaning and expected impact of Muhaimin Iskandar's speech acts, this research aims to gain insight into the pragmatic aspects of his speech in the context of debate. Through this analysis, the research aims to contribute to a deeper understanding of Muhaimin Iskandar's performance and communication strategies in debates. In this research, the researcher used a qualitative descriptive approach because this research discusses the phenomenon of speech acts contained in the inaugural Vice-Presidential Candidate Debate spoken by Muhaimin Iskandar, but it is not a statistical analysis. According to (Creswell & Creswell, 2018), qualitative research is a method for exploring and understanding the meaning of individuals or groups regarding social or humanitarian issues. The research process includes emerging questions and procedures, unique data collection based on participants' backgrounds, broad data analysis from specific to general themes, and the researcher's interpretation of the meaning of the data. Researchers also use a descriptive approach because the data is in the form of words and phrases Examining the locutionary and illocutionary acts of Muhaimin Iskandar, one of the vice-presidential candidates, in the first debate of the 2024 election, this research highlights the strategic use of language in political debates. This analysis provides valuable insight into how candidates use persuasive techniques, rhetorical strategies, and linguistic devices to effectively convey their messages and influence public opinion. The findings from this research can contribute to a better understanding of political communication and help the development of more comprehensive and differentiated approaches to analyzing political speech.